Sweat tests to diagnose cystic fibrosis in adults. Issue 6375 (30th April 1983) - Hodson, M E; Beldon, I; Power, R; Duncan, F R; Bamber, M; Batten, J C
Abstract : Twenty five patients with cystic fibrosis and 25 controls were studied to define a sweat sodium concentration in adults that could be taken as diagnostic of cystic fibrosis. Some of the controls had a sweat sodium concentration of over 50 mmol(mEq)/l, and thus cystic fibrosis should be diagnosed in an adult only when two measurements of sweat sodium concentration are above 70 mmol/l. In cases in which the sweat sodium concentration was borderline a suppression test using fludrocortisone improved the accuracy of diagnosis; this test entails recording the lowest concentration reached after administration of the drug. A scatter diagram of the baseline sweat sodium concentrations plotted against the lowest concentration attained after suppression with fludrocortisone may aid the diagnosis further.